Assessment of the control measures of the category A diseases of Animal Health Law: Newcastle disease. (2nd December 2021) - ; Nielsen, Søren Saxmose; Alvarez, Julio; Bicout, Dominique Joseph; Calistri, Paolo; Canali, Elisabetta; Drewe, Julian Ashley; Garin‐Bastuji, Bruno; Gonzales Rojas, José Luis; Gortázar Schmidt, Christian; Herskin, Mette; Michel, Virginie; et al.
Abstract: EFSA received a mandate from the European Commission to assess the effectiveness of some of the control measures against diseases included in the Category A list according to Regulation (EU) 2016/429 on transmissible animal diseases ('Animal Health Law'). This opinion belongs to a series of opinions where these control measures will be assessed, with this opinion covering the assessment of control measures for Newcastle disease (ND). In this opinion, EFSA and the AHAW Panel of experts review the effectiveness of: (i) clinical and laboratory sampling procedures, (ii) monitoring period and (iii) the minimum radius of the protection and surveillance zone, and the minimum length of time the measures should be applied in these zones. The general methodology used for this series of opinions has been published elsewhere. Several scenarios for which these control measures had to be assessed were designed and agreed prior to the start of the assessment. The monitoring period (21 days) was assessed as effective in non‐vaccinated chicken and turkey flocks, although large uncertainty remains surrounding the effectiveness of this period in vaccinated galliform flocks and flocks of other bird species. It was also concluded that the protection (3 km radius) and the surveillance (10 km radius) zones contain 99% of the infections from an infectious establishment. Recommendations provided for each of the scenarios assessed aim to support the European Commission in the drafting of further pieces of legislation, as well as for plausible ad hoc requests in relation to ND.